Enjoy writing your science thesis or dissertation : - Holtom, Daniel (Distributed by World Scientific Pub,Imperial College Press, 1999)
Enjoy Writing Your Science Thesis or Dissertation! is a complete guide to good dissertation and thesis writing. Written in an accessible style with apposite cartoons and anecdotes, it gives practical advice about how to plan, write, edit, present, and submit a successful thesis.